Pharmacy on a bicycle innovative solutions to global health and poverty - Bing, Eric G. (A BK currents book, 2013)
"Traditional pathways to delivering health care to the global poor are failing. Five million children die each year before their fifth birthday due to lack of basic health education, services, or low-cost treatments. Bing and Epstein show how focusing micro-innovations at the level of care is the way to end these grim health statistics"--